2020
DOI: 10.1186/s13018-020-01677-8
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the potential pharmaceutical mechanism of Guzhi Zengsheng Zhitongwan on rat bone and kidney based on the “kidney governing bone” theory

Abstract: Background: Guzhi Zengsheng Zhitongwan (GZZSZTW) is an effective Chinese medicinal formulation for the treatment of osteoarthritis (OA) designed according to the "kidney governing bone" theory, which has been widely used as a golden guide for treating bone and cartilage diseases in traditional Chinese medicine. The aim of this study was to explore the molecular mechanism underlying its effects on the bone and kidney. Methods: Preparation and quality control were performed as previously described. Since GZZSZTW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Previously, our group explored the molecular mechanisms related to bone development, growth, and regeneration using modern biology technologies, such as RNA-Seq and ITRAQ, and demonstrated that the underlying molecular mechanisms were highly consistent with the “kidney governing bones” theory. The results of this study coincide with our previous studies [ 6 10 ]. We also looked at markers for renal and testis function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previously, our group explored the molecular mechanisms related to bone development, growth, and regeneration using modern biology technologies, such as RNA-Seq and ITRAQ, and demonstrated that the underlying molecular mechanisms were highly consistent with the “kidney governing bones” theory. The results of this study coincide with our previous studies [ 6 10 ]. We also looked at markers for renal and testis function.…”
Section: Discussionsupporting
confidence: 93%
“…This means that the kidneys are responsible for the skeleton's growth and repair [ 5 ]. Previously, our group [ 6 10 ] explored the molecular mechanisms related to bone development, growth, and regeneration using modern biology technologies, such as RNA sequencing (RNA-Seq), and demonstrated that the underlying molecular mechanisms were highly consistent with the “kidney governing bones” theory. However, the precise molecular mechanism underlying “kidney governing bones” is still not clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment analysis of Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) was conducted by R function phyper to determine the biological functions and signaling pathways of those identified DEGs. The significance of enriched functional clusters and signaling pathways were determined based on the adjusted p value (Q value) of less than 0.05, which was calculated according to the Hypergeometric test and Bonferroni correction [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that MC3T3-E1 is a continuous source of osteoblast regeneration that avoids the need for repeated preparation of primary osteoblasts and has a better balance and homogeneity than primary osteoblasts [8,9]. Gujin Dan (GJD), developed by Professor Liu Bailing, is one of the typical Chinese medicine, which consists of 19 herbs acting synergistically, and has been used for decades in the treatment of cervical spondylosis, lumbar disc herniation, osteoarthritis and osteoporosis in the Department of Orthopaedics and Traumatology of Jilin Province Hospital of Traditional Chinese Medicin, China [10][11][12]. Clinically, the formulation is usually in the form of an oral pill for the treatment of patients with osteoporosis.…”
Section: Introductionmentioning
confidence: 99%